Nilai Budaya Tradisi Penarikan Pusaka Bedhah Bumi di Gunungkidul - Anggoro Mukti, Alfian; Endang Nurhayati; Suwardi; Heru Iswanto, Azis (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
The purpose of this study is to provide an in-depth explanation of the cultural values contained within the Bedhah Bumi heirloom retrieval tradition in Gunungkidul. This research also aims to contribute to the body of knowledge on culture, in order to ensure that Javanese culture—particularly traditions specific to certain areas—continues to be preserved. This study employs a qualitative research method. The research subject consists of the sole family that has inherited the leadership of the Bedhah Bumi heirloom retrieval tradition. The object of the research is the Bedhah Bumi heirloom retrieval tradition located in Kalurahan Gari, Kapanewon Wonosari, Gunungkidul Regency. Data were collected through observation and interviews. The collected data were then analyzed using a descriptive method. The validity of the data was ensured through theoretical validity, and its reliability was assessed through stability reliability. The results of this study reveal the cultural values embedded in the Bedhah Bumi heirloom retrieval tradition. The cultural values identified in this research include: the value of the relationship between humans and God, the value of the relationship between humans and nature, the value of the relationship between humans and society, the value of interpersonal relationships, and the value of the relationship between humans and themselves.